HBR's 10 must reads for new managers. - Hill, Linda A. 1956-; Watkins, Michael, 1956-; Walker, Carol A.; Reid, Erin.; Cialdini, Robert B.; Goleman, Daniel.; Ibarra, Herminia, 1961-; Gabarro, John J.; Ibarra, Herminia, 1961-; Oncken, William.; Watkins, Michael, 1956- (HBR's 10 must reads (Series), 2017)
"Develop the mindset and presence to successfully manage others for the first time. If you read nothing else on becoming a new manager, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you transition from being an outstanding individual contributor to a great manager of others. This book will inspire you to: develop your emotional intelligence; influence your colleagues with the science of persuasion; assess your team and enhance its performance; network effectively to achieve business goals and for personal advancement; navigate relationships with employees, bosses, and peers; get support from above; view the big picture in your decision-making * balance your team's work and personal life in a high-intensity workplace."--Publisher description.